HUBUNGAN SAINS DENGAN AGAMA PERSPEKTIF PEMIKIRAN IAN G BARBOUR - jendri jen (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2019)
The discussion between science and religion is a very interesting study to be studied in depth. It aims to strengthen science and religion, with the hope of contributing to the realm of education. This study uses a descriptive analysis of the relationship between science and religion according to Ian G Barbour's perspective. From the author's analysis of Ian G. Barbour's relationship between science and religion, it can be concluded that, Barbour made four typologies of the relationship between science and religion including the first, conflict typology, this typology involved materialism scientific scientificand literalism religious. Second, the typology of independence, this typology distinguishes the two types into different regions. Third, the typology of dialogue, this typology considers assumptions in scientific endeavors or parallels science and religion. To four typologies of integration, which is where this typology consisting of natural theology, theolgy of nature and systematic synthesis. Science and religion make a huge contribution to inclusive metaphysics. This research is a library research (library research). The source of research data consists of two forms, primary data (primary data), and secondary data (secondary data). To analyze this research, the method (content analysis) is used. Whereas in drawing conclusions using the deductive method in which the collected data is processed selectively and systematically then special conclusions are drawn which are the results of deductive research. The results of this study offer that if there is a conflict between science and religion, Ian G Barbaour offers an offer to science with religion is conflict, independence, dialogue and integrity. Keyword: Science, Religion, Ian G Barbour